The Analysis of Learning Needs of 5th Grade Elementary School Students for Indonesian Language Learning E-modules - Najichah, Amalia Fajriyyatin; Riski, Sarita (Madiha Press, 2024)
This study explores the educational requirements of fifth-grade elementary school students in order to develop efficient e-modules for Indonesian language instruction. Employing a descriptive qualitative methodology, the study uncovers students' inclinations towards engaging, multimedia-enhanced materials while also addressing difficulties like grasping intricate sentence structures and situating language within context. Insights from educators highlight shortcomings in existing teaching resources and emphasize the necessity for ongoing professional growth in the incorporation of technology within the educational framework. The results highlight the necessity of synchronizing e-module design with modern educational theories, promoting teamwork among educators, curriculum developers, and policymakers. This study offers practical recommendations aimed at enhancing student engagement, improving learning outcomes, and promoting independent learning within the context of Indonesian language education.